Discurso utópico e ação política: uma reflexão acerca da politéia platônica - Augusto, Maria das Graças de Moraes (Classica - Revista Brasileira de Estudos Clássicos, 1990)
Ancient greeks were not the creators of the word utopia but used extensively the utopic genre and mode to express their ideas on social organization. From Hippodamus of Miletus and Phaleas of Chalcedon, possibly inspired by Pythagoras and the first pythagoreans, to the sophists and Aristophanes, the theme slowly acquired philosophical content reaching its maturity with the platonic text. Plato's reflections on the relations between Philosophy and Politics, as presented in Letter VII, show that the Republic, while being a utopic construction, constitutes neither an ideal state (in the sense of being impossible to achieve and in oposition to real states) nor a historical imitation of political models (specially Sparta) but a possible course of political action.